2017
DOI: 10.1155/2017/4602952
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Peritoneal Macrophage Activation by Bougainvillea xbuttiana Extract and LPS and/or Interleukins

Abstract: Activation of macrophages may be one of the possible approaches in modulating inflammation. We previously reported that Bougainvillea xbuttiana extract showed an immunomodulatory activity. Here we compare the activation of macrophages exposed to B. xbuttiana extract and compare it with the other treatments such as LPS, IL-4, and IL-10. The cytotoxic effect of extract on peritoneal macrophages was determined by the technique of violet crystal staining. To verify the activation of macrophages we used the tests o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 25 publications
0
25
1
Order By: Relevance
“…The effect of the extract on the secretion of inflammatory mediators produced by LPS-treated macrophages was evaluated in cultures treated with the extract 1 hour before, 1 hour after or together with LPS. In previous studies, we have shown that the viability percentages of the macrophages cultures were between 90% for the first 24 hours and 75% from the 48 hours of exposures (data not shown) [ 10 , 12 ]. In all macrophage supernatants treated with LPS, increased production of proinflammatory mediators was observed.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…The effect of the extract on the secretion of inflammatory mediators produced by LPS-treated macrophages was evaluated in cultures treated with the extract 1 hour before, 1 hour after or together with LPS. In previous studies, we have shown that the viability percentages of the macrophages cultures were between 90% for the first 24 hours and 75% from the 48 hours of exposures (data not shown) [ 10 , 12 ]. In all macrophage supernatants treated with LPS, increased production of proinflammatory mediators was observed.…”
Section: Resultsmentioning
confidence: 94%
“…We have also demonstrated that B. x buttiana extract has the ability to activate murine macrophages in a manner similar to those IL-4 and IL-10 treated macrophages. The effects of this extract on macrophages were low cytotoxicity, increased percentages of vacuolation, hydrogen peroxide production, cell expansion, and phagocytosis [ 12 ]. The results obtained in this study demonstrate that the administration of the BxbO extract was able to inhibit the production of inflammatory mediators in both models, macrophages and serum of LPS-treated animals, and was able to guard the host from LPS-induced death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2a–c) ( F (1, 111) = 15.20, p < 0.001). This difference was observable as early as 6 h after LPS challenge and was sustained for at least 24 h. We selected the 6-, 12-, and 24-h time points for measurement of IL-6 as previous studies have shown increased IL-6 secretion using LPS-stimulated peritoneal macrophage cultures in mice at these time points, with linear increases in IL-6 up to the 24-h time point (Shacter et al 1993; Wollenberg et al 1993; Lin and Tang 2007; Lee et al 2015; Arteaga Figueroa et al 2017). The effect also appeared to be concentration and time dependent.…”
Section: Resultsmentioning
confidence: 99%